2014
DOI: 10.1038/sc.2014.23
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for cervical spondylotic amyotrophy: are signs of spinal cord involvement associated with the neurological prognosis?

Abstract: Objectives: The purpose of this study was to clarify the prognostic factors for cervical spondylotic amyotrophy (CSA). Methods: The authors retrospectively reviewed the medical records of 47 consecutive patients with CSA in whom the presence/ absence of the pyramidal tract sign was noted. We analyzed whether the age, sex, presence of diabetes mellitus, medication (vitamin B12), type of the most atrophic and impaired muscle, the muscle strength at the presentation, the presence of the pyramidal tract sign, magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
(10 reference statements)
2
4
0
Order By: Relevance
“…Moreover, all patients with C4/5 instability had no T2 HIA at C4/5, while T2 HIA at C3/4 was observed in two patients with C4/5 instability. Although Iizuka et al previously reported that the presence of T2 HIA on MRI was a prognostic factor for CSA, 17 T2 HIA on MRI was not common in patients with CSA, which was in line with the preceding studies. 17,18 This study also suggested that the damage to the neural tissue by cervical spine instability in CSA patients is located to AH or VNR in the cervical spine.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, all patients with C4/5 instability had no T2 HIA at C4/5, while T2 HIA at C3/4 was observed in two patients with C4/5 instability. Although Iizuka et al previously reported that the presence of T2 HIA on MRI was a prognostic factor for CSA, 17 T2 HIA on MRI was not common in patients with CSA, which was in line with the preceding studies. 17,18 This study also suggested that the damage to the neural tissue by cervical spine instability in CSA patients is located to AH or VNR in the cervical spine.…”
Section: Discussionsupporting
confidence: 89%
“…Although Iizuka et al previously reported that the presence of T2 HIA on MRI was a prognostic factor for CSA, 17 T2 HIA on MRI was not common in patients with CSA, which was in line with the preceding studies. 17,18 This study also suggested that the damage to the neural tissue by cervical spine instability in CSA patients is located to AH or VNR in the cervical spine. This may be why T2 HIA on MRI is an uncommon finding, even in CSA patients with cervical spinal instability.…”
Section: Discussionsupporting
confidence: 89%
“…Although it has been reported that several factors, including older age, lower manual muscle grade, multi-segmental compression, longer duration of symptoms, the presence of high signal intensity change on T2-weighted MR imaging, and pyramidal sign can be prognostic factors in the proximal type CSA, 5 , 16 , 23 , 24 our data suggests that the presence and severity of RCT can also be a poor prognostic factor in patients with proximal type CSA, at least in those who are managed conservatively.…”
Section: Discussionmentioning
confidence: 99%
“…According to the receiver operating characteristic analysis of a different study, Tauchi et al [15] recommended 4.3 months from symptom onset to surgery as the most appropriate timing with which to avoid an unfavorable postoperative course in patients with proximal type CSA. With respect to the preoperative physical status, the severity of the MMT grade and presence of long tract signs were related to poor recovery in some studies [5,13,15]. Electrophysiological examination has also shown that lower preoperative CMAP on the affected side than normal side is a predictably useful finding [4,6].…”
Section: Discussionmentioning
confidence: 99%